Attitudinal Changes Using Peer Education Training in the Prevention of HIV/AIDS: A Case Study of Youths in North Central Nigeria - Kamaldeen Abu-Saeed; Muhammad Buhari Abu-Saeed (Tabriz University of Medical Sciences, 2013)
Purpose: HIV/AIDS is a major public health issue. Studies have shown that young people between the ages of 15 to 24 years accounts for more than 40% of new HIV infections. However, new infections could be prevented if the desired impact is made on young people through interventions such as effective peer education program to improve their knowledge, attitude and practice. Therefore, this study is aimed at assessing the impact of peer education vis-a-vis attitudinal changes and practices on issues relating to HIV/AIDS among youths in North central Nigeria. Methods: This classical experimental study was carried out in three stages, that is: pre-intervention, intervention and post-intervention stages among students of Government High School, Ilorin between the ages of 15 and 24 years. The sample size was 80 students each for study and control groups. Proportional gender distribution was ensured in the selection and the sampling technique was multistage sampling technique. Data collection was through semi structured self administered pre and post evaluation questionnaire. Peer education training and forth night mentoring sessions was conducted for the study group. Impact of the intervention was assessed after eight weeks. Results: Analysis of the result shows that out of the sixteen questions asked on respondents‟ attitude, only four showed statistical significance between the study and control group before the intervention which shot up to eleven after intervention. Also, the frequency of those having bad practices regarding prevention of HIV/AIDS also reduced after intervention. This reduction was much more in many instances when compared to the control group. Conclusion: This study has revealed that peer education training among youth can go a long way in educating them on issues relating to HIV/AIDS prevention. It can also bring about attitudinal changes and better practices that may help in reducing incidence and prevalence of HIV/AIDS in our society.